Evaluating productive performance: A new approach based on the product-mix problem consistent with Data Envelopment Analysis. (March 2017) - Aparicio, Juan; Pastor, Jesús T.; Vidal, Fernando; Zofío, José L.
Abstract: We propose a new approach to estimate technical coefficients from a set of Decision Making Units (DMUs) under the assumption that their production plans are set by process engineers through Linear Programming (LP) techniques. The idea behind this approach is that most manufacturing and agricultural firms routinely resort to LP-based modeling in their decision making processes in order to plan output production and, therefore, this particularity should be taken into account when estimating their technical efficiency. A usual model of LP for these sectors is the so-called product-mix problem, which we relate to a standard Data Envelopment Analysis (DEA) model in terms of the Directional Distance Function. In this paper, we finally show how to estimate the technical coefficients of a sample of Andalusian farms in Spain and how this information can be seen as a complement to the usual by-products associated with estimating technical efficiency by DEA. Highlights: We relate the product-mix problem to notions of the field of technical efficiency. A model for estimating technical coefficients from a data sample is introduced. The new approach complements the results obtained with the standard DEA method. The relationship between DEA and the new methodology is shown resorting to the DDF. The new methodology is illustrated through an empirical example.